Comment on empirical evidence for the design of public lighting. (July 2016) - Fotios, Steve
Abstract: A recent article (Peña-García et al., 2015) presented conclusions regarding the benefits of road lighting for pedestrians. Here it is demonstrated that those conclusions were drawn from incomplete evidence, in one case because the experimental designs leads only to a trivial solution and in a second case because of an incomplete search of the literature.